Zimbabwe's indigenization policy: correcting colonial injustices or campaigning strategy? - Nciizah, Elinah (Midlands State University, 2016)
Indigenization policy, which became topical in 2011 and 2012 amidst talks of upcoming elections, stirred a lot of controversy in Zimbabwe. It has been argued that this policy has been undertaken as a way of empowering people. This paper seeks to join the ongoing debates by examining the Indigenization and Economic Empowerment Act. The main thrust of the paper lies in examining the objectives of the policy, the intended beneficiaries and its impact on development in general. In addition, the paper examines whether the Act was really about redistributive justice or a political move by ZANU PF party to garner support. The paper therefore argues that as much as the indigenization policy is meant to benefit and empower the black people and addressing colonial injustices, there are motives behind its implementation. Under such lenses it becomes significant to examine Zimbabwe‟s move towards the indigenization policy.